If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1 = 15 + 5x Reorder the terms: -1 + 2x = 15 + 5x Solving -1 + 2x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -1 + 2x + -5x = 15 + 5x + -5x Combine like terms: 2x + -5x = -3x -1 + -3x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 -1 + -3x = 15 + 0 -1 + -3x = 15 Add '1' to each side of the equation. -1 + 1 + -3x = 15 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = 15 + 1 -3x = 15 + 1 Combine like terms: 15 + 1 = 16 -3x = 16 Divide each side by '-3'. x = -5.333333333 Simplifying x = -5.333333333
| -6t+g=6 | | -6t+6=6 | | -0.0912+0.96v=-0.168 | | -0.0912+0.96=-0.168 | | 3t+4g=6 | | 3t+2d=52 | | 4x^3+6x^2-2x+9=0 | | 3x-6(2x-10)=159 | | 3t+2d=62.5 | | y=y(600-3y) | | 22x+13=-5-7x | | 8(4x-5)=9(x-6)-5 | | -84-10x=8+24 | | 86x-3x=10x+21 | | 6B=420 | | 3x-1=3x+8 | | -3z-6=0 | | 8=-8x-8 | | 5(0)-y=-7 | | -9=-5x+19 | | 9e^3x+2=54 | | 7(x+2)=(5x+1)/2 | | (x+2)=(5x+1)/2 | | (y-5)-(6+6)=7y | | x+20=3x-4 | | 18x+27=9x+36 | | c=200+25x | | -2/3y=10.6 | | 2*5x=10*2x | | 5a-10b-10a+6b/2a | | 8x+7=16+5x | | (5a-10b-10a+6b)/2a |